Cultural Components of Technology and Its Implications for Adult Education - Jim Berger (Adult Education Research Conference, 2008)
This article seeks to describe technology and how its design and use embodies values embedded in the dominant culture and is meant to support the hegemonic goals of the dominant culture while suppressing the growth and development of marginalized groups and propose a means of researching between technology and adult learners.
Keywords: culture of technology; critical theory; adult learning; cultural studies; science and technology studies